1986
DOI: 10.1159/000260988
|View full text |Cite
|
Sign up to set email alerts
|

Caries-Preventive Effect of Duraphat® Varnish Applications versus Fluoride Mouthrinses: 5-Year Data

Abstract: The caries-preventive effect of Duraphat® lacquer versus fluoride mouthrinses was evaluated in a 5-year clinical trial. The lacquer group received Duraphat application every 6th month and a placebo rinse every 2nd week during the school year. The fluoride rinse group received a 0.2% sodium fluoride rinse every 2nd week during the school year and a placebo lacquer every 6th month. All children received regular dental examination and treatment in clinics established by the municipality in which the study took pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
1

Year Published

1987
1987
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 5 publications
(5 reference statements)
0
20
1
Order By: Relevance
“…The results disagree with those of Kirkegaard et al [1985] who found no dif ference between the effect of Duraphat and fortnightly rinses. This may be due to the lower age and lesser caries activity among children in that study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The results disagree with those of Kirkegaard et al [1985] who found no dif ference between the effect of Duraphat and fortnightly rinses. This may be due to the lower age and lesser caries activity among children in that study.…”
Section: Discussioncontrasting
confidence: 99%
“…This may be due to the lower age and lesser caries activity among children in that study. The compli ance in the rinsing group may also have been higher in the study of Kirkegaard et al [1985], although no evidence of this is available. In this study, no extra attempt was made to influence the participation in order to find out the effect of the pro gramme with all its restraints.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Seppa and Pollanen [1987] reported on a clinical study where Duraphat varnish was more effective than fluoride rinsing with a 0.2% NaF solution which in turn was better than FluorProtector®. However, neither Bruun et al [1985] nor Kirkegaard et al [1986] demonstrated a superi or effect of varnishes over mouthrinses.…”
Section: Combinations O F Fluoride Mouthrinsing and Other Fluoride Mementioning
confidence: 81%
“…The drop-out rate during the trial was a little lower than the 25-26% in some of our previous trials [Poulsen et al, 1981;Kirkegaard et al, 1986] and slightly higher for the 1989-92 cohort (23%) than for the 1990-93 cohort (17%). This difference may have been generated by the negative effect of the media's comments on the trial.…”
Section: Discussionmentioning
confidence: 50%